2008
DOI: 10.2147/copd.s4257
|View full text |Cite
|
Sign up to set email alerts
|

Geographic differences in clinical characteristics and management of COPD: the EPOCA study

Abstract: Aims: Data on differences in clinical characteristics and management of COPD in different countries and settings are limited. We aimed to characterize the profi le of patients with COPD in a number of countries and their treatment in order to evaluate adherence to recommendations of international guidelines. Method: This was an observational, international, cross-sectional study on patients with physician-diagnosed COPD. Demographic and clinical characteristics, risk factors, and treatment were collected by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 40 publications
4
48
1
2
Order By: Relevance
“…4 In an international, multicentre study reviewing the geographic differences in management of COPD patients, LAMA (tiotropium) usage was 36% and combined use of LABA and inhaled corticosteroids (ICS) was 46% globally. 16 In Hong Kong, the usage of LAMA was less than 2% and combined LABA/ICS was only 13%. 16 The higher exacerbation rate in Hong Kong might be related to the lower prescription rates for LAMA and/or LABA/ICS drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 In an international, multicentre study reviewing the geographic differences in management of COPD patients, LAMA (tiotropium) usage was 36% and combined use of LABA and inhaled corticosteroids (ICS) was 46% globally. 16 In Hong Kong, the usage of LAMA was less than 2% and combined LABA/ICS was only 13%. 16 The higher exacerbation rate in Hong Kong might be related to the lower prescription rates for LAMA and/or LABA/ICS drugs.…”
Section: Discussionmentioning
confidence: 99%
“…16 In Hong Kong, the usage of LAMA was less than 2% and combined LABA/ICS was only 13%. 16 The higher exacerbation rate in Hong Kong might be related to the lower prescription rates for LAMA and/or LABA/ICS drugs. Thus, adherence to treatment guidelines appears insufficient, and may be partly related to cost concerns.…”
Section: Discussionmentioning
confidence: 99%
“…However, Spanish study reported that sputum production and cough had the highest circadian variability (6), whereas breathlessness was reported as the most common and troublesome symptom among European populations (5). All these fluctuations could be attributed to geographic variations, genetic background, exposure to risk factors and management strategies around the world (12)(13)(14).…”
Section: Prevalence Variation and Severity Of Copd Symptomsmentioning
confidence: 99%
“…Patients included in clinical trials have a mean of 1-3 exacerbations per year [8]. In an international observational study there was a significant relationship between the severity of airflow obstruction and an increased number of exacerbations per year; however, this relationship was weak, indicating that many other factors influence the risk of having an exacerbation [9].…”
Section: Definition and Frequency Of Exacerbationsmentioning
confidence: 99%
“…These products have been frequently used [9], but the scientific evidence supporting their use has traditionally been insufficient.…”
Section: Mucolyticsmentioning
confidence: 99%